Wavelet Transformation and Spectral Subtraction Method in Performing Automated Rindik Song Transcription - Yuriko Christian; I Dewa Made Bayu Atmaja Darmawan (Faculty of Computer Science - Universitas Indonesia, 2022)
Rindik is Balinese traditional music consisting of bamboo rods arranged horizontally and played by hitting the rods with a mallet-like tool called